Transformative-Critical Education Paradigm: Investigating the Influence of Paulo Freire and Moeslim Abdurrahman in Ikatan Pelajar Muhammadiyah (1998-2008) - Azaki Khoirudin (Universitas Muhammadiyah Surakarta, 2017)
This study investigated the influence of Paulo Freire’s criticaleducation and Moeslim Abdurrahman’s Transformative Islam in IkatanPelajar Muhammadiyah (IPM). The problem statement was formulated:to what extent Freire and Moeslim influence the educational thoughtand practice of education in IPM? By using discourse analysis, thisstudy revealed that the discourse and practice of critical-transformativeeducation has evolved in IPM since the reform era in 1998-2008.The Discourse of critical education and Transformative Islam areintertwined into “Manifesto of Transformative Critical Movement”incorporated in the educational guideline of IPM members. Thistransformative-critical discourse has encouraged IPM becoming apopulist student organization. Afterward, the discourse and practice ofthis organization’s movements is accentuated by the criticism towardsinjustice and the struggle towards social transformation